Protocol for a Single-Center Randomized Controlled Trial of Percutaneous Coronary Intervention Via Distal Transradial Access Versus Transradial Access - Minghao Liu; Huanhuan Wang; Lijian Gao; Jue Chen; Cui Cheng; Ying Song; Hao Zhang; Wei Yu; Xinyue Lang; Honghui Zhao; Jinwei Zhai; Yana Tong; et al. (Cardiovascular Innovations and Applications)
Background: Although transradial access (TRA) has become the main vascular access for coronary intervention, its high radial artery occlusion rate limits its application in some patients. Studies have shown that compared with TRA, distal transradial access (dTRA) with the snuffbox area or the Hegu acupoint area as the puncture point significantly decreases the incidence of radial artery occlusion. However, no randomized controlled study has confirmed the safety and efficacy of coronary artery intervention via dTRA in China. Methods and analyses: This single-center, prospective, randomized controlled, superiority open-label study will enroll 428 consecutive patients with coronary heart disease undergoing percutaneous coronary intervention as the study population. After preoperative evaluation, the participants will be randomly divided into a study group (dTRA) and control group (TRA) in a 1:1 ratio. The primary endpoint (radial artery occlusion at 24 hours after operation) and secondary endpoint events will be evaluated and recorded. Study registration: This study has been registered in the Chinese Clinical Trial Registry (registration number: ChiCTR2300073902).